Homeric Catalogues Between Tradition and Invention - Nova, Isabella (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2019)
This contribution aims at showing how a traditional list of names could be varied by poets with the addition of new ones sharing the same features, with a special focus on the Nereids’ names. A comparison between the catalogue of Nereids in the Iliad (XVIII 39–49) and the one in the Theogony (Theog. 243–264) shows that whilst some names are traditional and some others seem to be invented ad hoc, they all convey relaxing images (sea, nature, beauty, or gifts for sailors). This list of names did not become a fixed one in later times either: inscriptionson vase-paintings of the 5th century preserve names different than the epic ones. Even Apollodorus (I 2, 7) gives a catalogue of Nereids derived partly from the Iliad and partly from the Theogony, with the addition of some names belonging to another group of deities (the Oceanids) and other forms unattested elsewhere but with the same features of the epic ones. A further comparison between a catalogue of Nymphsin the Georgics (IV 333–356) and its reception in the work of Higynusproves that adding new names to a traditional list is a feature not only of oral epic poetry, but also of catalogues composed in a literate culture.
Keywords: Homer; Iliad; Hesiod; Theogony; Apollodorus; Virgil; Hyginus; Nereids